"Trans”- Modernism: A Path towards Peaceful Coexistence in a Diverse World to Exist is to Co-Exist - Lakka, A. (University of jaffna, 2024)
In today’s increasingly interconnected global society, the challenges of nurturing peaceful coexistence among a mosaic of cultures and religions have surged to the forefront. This exploration delves deeply into the potential of “trans”-modernism as a philosophical framework to meet these challenges and lay the foundation for harmonious interactions and collaborations. By countering Samuel P. Huntington’s thesis on the clash of civilizations that propose future conflicts rooted in cultural and religious difference, this work underscores the profound importance of dialogue, cooperation, and mutual understanding across diverse cultural and religious landscapes. “Trans”- modernism emerges as a constructive response to the discerned failures of modernism, a philosophy which held undue emphasis on rationality and individualism, spiraling into environmental degradation, social inequality, and political polarization. The premise of transmodernism lies in its commitment to interconnectedness, diversity, and sustainability, advocating a reformed approach to social and political thought. One significant argument against Huntington’s clash of civilizations theory is the recognition of abundant diversity within each civilization. An often-underestimated aspect is that people from diverse cultures frequently share more similarities than anticipated. By honoring the agency of individuals and championing peaceful interactions, transmodernism robustly challenges the notion of intrinsic antagonism between civilizations. In the context of countries known for vibrant cultural and religious diversity, such as India, the implications of transmodernism hold special significance. The adoption of a transmodernist perspective can facilitate a solid framework for promoting peaceful coexistence among the diverse religious and cultural communities within India. Through a comprehensive appreciation of the interwoven connectedness of these communities, and by valuing diversity and championing sustainable practices, India can sow the seeds for a society marked by harmony, mutual respect, and the joyful celebration of cultural and religious diversity.
Keywords: Transmodernism; Interconnectedness; Peaceful coexistence